Modeling the influence of the intensive crystallization level height on the cumulonimbus cloud parameters. Issue 1 (August 2021) - Kuznetsov, A; Simakina, T; Kryukova, S
Abstract: The importance of information on the ice particles amount and formation height in understanding the processes taking place in a cumulonimbus cloud is shown. In radar meteorology the intense crystallization level NIC is one of the criteria for the cloud transition to the thunderstorm activity stage. Modeling of a cumulonimbus cloud parameters with the intensive crystallization level height change has been carried out. With an increase in NIC there is a decrease in the hydrometeors number entering the crystallized area, an increase in the area volume with the highest water content in the cloud center, its rise, and a change in the orientation of the large drops «nursery» with a water content of more than 8 g/m 3 from horizontal to vertical shape. The dependence of the hydrometeor size in the central part of the cloud jet and the lifetime on the NIC level has been detected.